Fundamentals of medical-surgical nursing : a systems approach - Brady, Anne-Marie, 1965-; McCabe, Catherine; McCann, Margaret (Fundamentals of educational planning., 2014)
"Fundamentals of Medical Surgical Nursing is a comprehensive yet accessible textbook on medical and surgical nursing designed to inform and guide learning related to the nursing care of the adult patient. It provides a foundation in anatomy and physiology, pathophysiology, medical management, and nursing care for the spectrum of adult health conditions. Divided into two sections, the first looks at common principles underlying medical and surgical nursing practice. In section two, students will be able to apply relevant anatomy and physiology to enhance their understanding and inform their nursing care of medical and surgical conditions"--Provided by publisher